Psychotic experiences are associated with health anxiety and functional somatic symptoms in preadolescence. (5th October 2018) - Rimvall, Martin K.; Jespersen, Cecilia Pihl; Clemmensen, Lars; Munkholm, Anja; Skovgaard, Anne Mette; Verhulst, Frank; van Os, Jim; Rask, Charlotte Ulrikka; Jeppesen, Pia
Abstract : Background: Health anxiety (HA) is an increasing public health problem related to increased health service costs, and associated with functional somatic symptoms (FSS) and considerable personal suffering. Abnormal bodily experiences which may resemble HA and FSS are common in psychotic disorders, but a potential link between HA and psychosis vulnerability in childhood is largely unexplored. The current study estimates the association between subclinical psychotic experiences (PE) and HA and FSS in a general population cohort of preadolescents. Methods: The study population consisted of 1, 572 11–12‐year‐old children from the Copenhagen Child Cohort 2000. PE were comprehensibly assessed as either present or not present using the Kiddie Schedule of Affective Disorders and Schizophrenia psychosis section. HA and FSS were assessed by self‐report on validated questionnaires. Additional variables on general psychopathology, puberty, and chronic somatic illness were also obtained. Results: Psychotic experiences were associated with the top 10% high scores of HA (Odds Ratio (OR) 3.2; 95% CI: 2.1–4.8) and FSS (OR 4.6; 95% CI: 3.1–6.9) in univariate analyses. After mutual adjustment, the association was reduced to (HA: OR 2.3; 95% CI: 1.5–3.5; FSS: OR 3.7; 95% CI: 2.4–4.7), suggesting interdependence. Further adjustment for potential confounders and general psychopathology only reduced the associations slightly: HA OR 2.2 (95% CI: 1.4–3.4); FSS OR 3.3 (95% CI: 2.1–5.2). Secondary analyses of subdimensions of HA showed that PE were associated with fears (OR 3.0; 95% CI: 2.0–4.6) and daily impact of HA symptoms (OR 5.0; 95% CI: 3.4–7.5), but not help seeking (OR 1.2; 95% CI: 0.7–2.1). Conclusions: This is the first study to investigate the associations between PE and HA and FSS, respectively. PE were significantly associated with HA and FSS over and above general psychopathology in preadolescence. Individuals with PE expressed high levels of health‐related fears and daily impact, but no corresponding help‐seeking behavior.